DESIGNING ENGLISH FOR SPECIFIC PURPOSE SYLLABUS FOR EDITING COURSE - Wieka Barathayomi; Dina Rachmawati; Ledy Nurlely; Rita Handayani (Journal of English Language Studies, 2016)
The objective of this research is to design an English for specific purposes syllabus for Editing Course. This research used Research and Development method. This research consists of two main activities: 1) need analysis and 2) designing an English for specific purposes syllabus for editing course. The data for this research were collected through an open-ended questionnaire consisting of 7 items, and study of literature. The open-ended questionnaire was used to collect data about students’ understanding of Editing. The study of literature was used as supporting theories to design and develop Syllabus for Editing Course. The study showed that the syllabus of Editing Course need to be designed based on prerequisite knowledge and skills of an Editor, such as knowledge and skills in mechanical, content, and language editing. Keywords: Syllabus Design, Need Analysis, ESP, and Editing